Crosstalk among plant hormone regulates the root development - Yuru Ma; Jiahui Xu; Jiahong Qi; Dan Zhao; Mei Jin; Tuo Wang; Yufeng Yang; Haojia Shi; Lin Guo; Hao Zhang (Plant Signaling & Behavior)
The plant root absorbs water and nutrients, anchors the plant in the soil, and promotes plant development. Root is developed from root apical meristem (RAM), which is formed during embryo stage and is maintained by dividing stem cells. Plant hormones have a predominant role in RAM maintenance. This review evaluates the functional crosstalk among three major hormones (auxin, cytokinin, and brassinolide) in RAM development in Arabidopsis, integrating a variety of experimental data into a regulatory network and revealing multiple layers of complexity in the crosstalk among these three hormones. We also discuss possible directions for future research on the roles of hormones in regulating RAM development and maintenance.